Upaya Peningkatan Status Gizi Balita yang Mengalami Stunting dengan Pelatihan Kreasi Menu Seimbang atau Bergizi - Siti Zuraida Muhsinin; Nurul Hidayati; Ade Irma Fitria Ningsih; Herni Sulastien; Abdul Rahman Al-Khuzaifi (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
The result of the preliminary study in Apit Aik hamlet has found that the 7 toddlers have stunted problems and from the anamnesis the study has found that mothers lack knowledge about how to fulfill the balanced nutrition for toddlers. As a health institution, the faculty of health sciences tried to participate in efforts to reduce stunting rates by conducting counseling activities and training in the manufacture of complementary feeding foods. The purpose of this community service activity is to help mothers with stunted children understand what stunting is, balanced/nutritious nutrition, and can make processed complementary foods for their toddlers. The location of this community service activity is Apit Aik hamlet, Gunung sari District, West Lombok, and West Nusa Tenggara. The target is mothers with stunting children, the 7 people in total. In the process of activities, the methods were used lectures, discussions, demonstrations, and also by giving leaflets to participants. Before and after the activities, the participants have given a questionnaire to evaluate the material provided. The progress of the community service activity evaluation showed an increase in participants' learning from the lack level of the 4 people, 57.1% to the level of good knowledge of the 6 people or 85.7%. Based on the result, it is significant to carry out similar activities followed by an evaluation of the nutritional status of children under five with stunting. ABSTRAK Hasil studi pendahuluan di dusun Apit Aik ditemukan 7 orang batita mengalami stunting dan dari anamnesis didapatkan adanya pengetahuan yang kurang pada ibu tentang bagaimana pemenuhan nutrisi seimbang pada balita. Sebagai institusi kesehatan, fakultas ilmu kesehatan berusaha ikut berpartisipasi dalam upaya menurunkan angka stunting, dengan melakukan kegiatan penyuluhan dan pelatihan pembuatan makanan MP-ASI. Tujuan kegiatan pengabdian masyarakat ini adalah membantu ibu dengan anak stunting untuk memahami apa itu stunting, gizi seimbang/bergizi serta dapat membuat olahan makanan bergizi MP-ASI untuk balita mereka. Kegiatan pengabdian masyarakat ini berlokasi di dusun Apit Aik, Kecamatan Gunungsari, Lombok Barat, Nusa Tenggara Barat. Sasarannya adalah ibu dengan anak stunting yang berjumlah 7 orang. Dalam proses kegiatan metode yang digunakan adalah ceramah, diskusi dan demonstrasi, serta pemberian leaflet pada peserta. Sebelum dan setelah kegiatan peserta diberikan kuesioner untuk dapat mengevaluasi materi yang diberikan. Hasil evaluasi memperlihatkan terjadi peningkatan pengetahuan peserta dari tingkat pengetahuan yang kurang sebanyak 4 orang atau 57.1% menjadi tingkat pengetahuan baik sebanyak 6 orang atau 85,7%. Berdasarkan hal tersebut diatas penting untuk dilakukan kegiatan serupa dengan diikuti evaluasi pada status gizi balita dengan stunting.